2022
DOI: 10.1371/journal.pone.0262287
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported symptoms as predictors of SARS-CoV-2 infection in the general population living in the Amsterdam region, the Netherlands

Abstract: Introduction Most COVID-19 symptoms are non-specific and also common in other respiratory infections. We aimed to assess which symptoms are most predictive of a positive test for SARS-CoV-2 in symptomatic people of the general population who were tested. Methods We used anonymised data of all SARS-CoV-2 test results from the Public Health Service of Amsterdam from June 1,2020 through August 31, 2021. Symptoms were self-reported at time of requesting a test. Multivariable logistic regression models with gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
2
0
1
Order By: Relevance
“…For SARS-CoV-2, we identified only sore throat as a positive predictor of infection. Contrary to our findings, other studies found more symptoms associated with SARS-CoV-2 infection, including fever, cough, headache, loss of smell or taste and myalgia [24,25]. The small number of SARS-CoV-2 cases detected in our study may have contributed to the poor association of cases with clinical manifestations.…”
Section: Discussioncontrasting
confidence: 99%
“…For SARS-CoV-2, we identified only sore throat as a positive predictor of infection. Contrary to our findings, other studies found more symptoms associated with SARS-CoV-2 infection, including fever, cough, headache, loss of smell or taste and myalgia [24,25]. The small number of SARS-CoV-2 cases detected in our study may have contributed to the poor association of cases with clinical manifestations.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, the most frequently reported symptoms were general fatigue, headache, fever, anosmia and/or ageusia, and cough, respectively, with no significant differences between refugees and citizens. These symptoms were also reported in many previous studies from different regions [ 35 37 ].…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, the most frequently reported symptoms were general fatigue, headache, fever, anosmia and/or ageusia, and cough, respectively, with no significant differences between refugees and citizens. These symptoms were also reported in many previous studies from different regions [35][36][37]. Interestingly, the results obtained in this study demonstrated that the perceptions and experiences of COVID-19 vaccination were different between refugees and citizens.…”
Section: Discussionsupporting
confidence: 84%